2020
DOI: 10.1177/0743558420979124
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Youth’s Reported Social and Moral Transgressions and Strategies for Self-Correction

Abstract: The aim of this study was to explore Chinese adolescent’s social and moral transgressions and strategies for self-correction. For this study, following protocols that have been approved by an Institutional Review Board, 61 Chinese adolescents living in Guangzhou—distributed across three age groups: 10- to 11-year-olds ( N = 21, Mage = 11.03 years, SD = 0.43 years), 12- to 13-year-olds ( N = 20, Mage = 12.92 years, SD = 0.35 years), and 15- to 16-year-olds ( N = 20, Mage = 16.15 years, SD = 0.30 years)—particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…The finding that adolescents in this study often referenced keeping secret activities in direct response to parental expectations that their time be spent on academics, is in keeping with prior research that has shown that academic study permeates many aspects of Chinese children’s and adolescents’ life. For example, Liu and Midgette (2022) found that academic considerations were infused throughout students’ experiences and justifications for their social transgressions at home and at schools. Research also revealed that schoolwork was a major source of adolescent-parent conflicts in Mainland China; while American adolescents mainly had conflicts with their parents over housework (Cao & Tam, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that adolescents in this study often referenced keeping secret activities in direct response to parental expectations that their time be spent on academics, is in keeping with prior research that has shown that academic study permeates many aspects of Chinese children’s and adolescents’ life. For example, Liu and Midgette (2022) found that academic considerations were infused throughout students’ experiences and justifications for their social transgressions at home and at schools. Research also revealed that schoolwork was a major source of adolescent-parent conflicts in Mainland China; while American adolescents mainly had conflicts with their parents over housework (Cao & Tam, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the importance of investigating how across development individuals come to identify and make sense of their social and moral transgressions (Liu & Midgette, 2022; Midgette, 2018). In particular, this line of work highlights the value of investigating what individuals are indeed learning “from their mistakes” (i.e., transgressions they themselves consider transgressive; Liu & Midgette, 2022, p. 21) by investigating why they consider it problematic, as this may inform educational interventions to best support their developing moral agency (e.g., help them to self-correct in the future). However, prior initial research has been limited to studying children’s and adolescents’ experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, conventional transgressions concern violation of social rules and norms, and their rightness or wrongness is dependent on social agreement and/or authority dictates. Moreover, personal transgressions would involve only violation of one’s own personal expectations or preferences (e.g., Liu & Midgette, 2022; Midgette, 2018). This domain distinction has been found to occur cross-culturally (Chen-Gaddini, 2012; Hasebe et al, 2004; Neff, 2001; Smetana, 2006; Yau & Smetana, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations